2019
DOI: 10.1021/acs.nanolett.9b05056
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Active Control of a Collective Polariton Mode and Polaritonic Band Gap in Few-Layer WS2 Strongly Coupled with Plasmonic Lattices

Abstract: Two-dimensional semiconductors host excitons with very large oscillator strengthsand binding energies due to significantly reduced carrier screening. Two-dimensional semiconductors integrated with optical cavities are emerging as a promising platform for studying strong light-matter interactions as a route to explore a variety of exotic many-body effects. Here, in few-layered WS2 coupled with plasmonic nanoparticle lattices, we observe the formation of a collective polaritonic mode near the exciton energy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 66 publications
(117 reference statements)
1
31
0
Order By: Relevance
“…[11] Fabry-Perot and plasmonic cavities have been widely used to enhance the light-matter interaction of TMDC monolayers. [12][13][14][15][16][17][18][19][20][21][22][23] However, the fabrication process may be complex, and monolayer's optical properties may be degraded for the former. Simultaneously, the latter suffers from large intrinsic loss, which may generate heat and thus degrade the performance.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Fabry-Perot and plasmonic cavities have been widely used to enhance the light-matter interaction of TMDC monolayers. [12][13][14][15][16][17][18][19][20][21][22][23] However, the fabrication process may be complex, and monolayer's optical properties may be degraded for the former. Simultaneously, the latter suffers from large intrinsic loss, which may generate heat and thus degrade the performance.…”
Section: Introductionmentioning
confidence: 99%
“…Substrate engineering could also facilitate novel opportunities for tailoring the functionality of diffractive arrays and metasurfaces. In particular, the high quality factor, spatially delocalized character and unique dispersion properties of surface lattice resonances 37,60,61 supported by nanoantenna arrays render them as interesting candidates for polaritonic device technologies, but the additional design scope conferred by the substrate material has not yet been thoroughly explored. Recently, lattices of localized polariton condensates have shown the capability of forming topologically protected states 62,63 and simulating many-body Hamiltonians.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the charge density can be tuned in a vast range through gating, which provides an ideal playground for efficient electro-optical modulations. Two research groups independently demonstrated that the optical properties 63,64 , such as absorption and PL, can be The electrical tunability of refractive index (or dielectric permittivity) also enables the dynamic control of the strong light-matter interactions in 1L-TMDC 399,400,[460][461][462] . For instance, Chakraborty et al…”
Section: Electric Tuningmentioning
confidence: 99%